Fetal airway management on placental support: Limitations and ethical considerations in seven cases. (November 2013) - Barthod, G.; Teissier, N.; Bellarbi, N.; Viala, P.; Oury, J. F.; Dray, G.; Vuillard, E.; Michel, J.; Van Den Abbeele, T.
Abstract : The aim of this study was to evaluate the paediatric and maternal outcome after ex utero intrapartum treatment (EXIT). A retrospective review was carried out of the medical charts (gestational age, circumstances of diagnosis, multidisciplinary prenatal decision, date of surgery, paediatric and maternal outcome) of all the fetuses eligible for/delivered via the EXIT procedure in our paediatrics and obstetrics tertiary care and teaching centre, between October 2004 and May 2011. Seven fetuses with cervical teratoma, epignathus tumour or congenital high airway obstruction syndrome (CHAOS) were included in our study. Two pregnancies were terminated and five fetuses were delivered alive. The airway was secured in all five cases (two endotracheal intubations and three tracheostomies). No maternal complications were observed. On average, babies were delivered at 32 gestational weeks, and spent 31 days in the intensive care unit. All but one baby were ventilated for 18 days. Long-term paediatric outcome was favourable. It is concluded that airway management by the EXIT procedure has become an efficient technique. A multidisciplinary prenatal assessment is essential in order to select appropriate cases.